Potensi Cryptocurrency dalam Pendanaan Proliferasi Senjata Pemusnah Massal - Kurnia, Kana (Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK), 2024)
Cryptocurrencies have grown rapidly and are used in various cross-border transactions. The negative impact of cryptocurrencies includes the misuse of crimes, especially in funding the weapons of mass destruction (WMD) proliferation. This article examines how cryptocurrency can be utilized in WMD proliferation funding and the challenges faced in overcoming this problem. The method used is a normative research method with a conceptual approach. The research found that cryptocurrency characteristics such as high anonymity and cross-border transactions make it easier for WMD proliferation funding perpetrators to hide funding traces. The lack of transparency in the blockchain adds to the difficulty in tracking WMD proliferation funds. The suggestion from this research is that there is a need for stronger international cooperation and a financial system that can detect and prevent the spread of nuclear material.